Immunohistochemical study of p16INK4A and survivin expressions in cervical squamous neoplasm. - Tan, Geok Chin; Sydee, Norlatiffah; Syed Husain Shahabuddin, Sharifah Noor Akmal; Ghazali, Razmin; Mohd Sidik, Shiran; Mohd Dali, Ahmad Zailani Hatta; Ng, Paul Hock Oon (Medknow Publications, 2010)
Introduction: Cervical cancer is the second most common cancer affecting Malaysian women. Despite the implementation of pap smear screening, many women are still diagnosed only in the advanced stage of cervical cancer. This could partly be due to failure of detection of its precursor lesions; hence the need to search for novel biomarkers to assist in the screening and diagnosis of cervical neoplasia. This study aims to determine the expression of p16 INK4A and survivin as possible predictive biomarkers in cervical squamous neoplasm.